Characteristics and Application of Rhodopseudomonas palustris as a Microbial Cell Factory - Li, Meijie; Ning, Peng; Sun, Yi; Luo, Jie; Yang, Jianming (Frontiers in Bioengineering and Biotechnology, 2022)
Rhodopseudomonas palustris, a purple nonsulfur bacterium, is a bacterium with the properties of extraordinary metabolic versatility, carbon source diversity and metabolite diversity. Due to its biodetoxification and biodegradation properties, R. palustris has been traditionally applied in wastewater treatment and bioremediation. R. palustris is rich in various metabolites, contributing to its application in agriculture, aquaculture and livestock breeding as additives. In recent years, R. palustris has been engineered as a microbial cell factory to produce valuable chemicals, especially photofermentation of hydrogen. The outstanding property of R. palustris as a microbial cell factory is its ability to use a diversity of carbon sources. R. palustris is capable of CO2 fixation, contributing to photoautotrophic conversion of CO2 into valuable chemicals. R. palustris can assimilate short-chain organic acids and crude glycerol from industrial and agricultural wastewater. Lignocellulosic biomass hydrolysates can also be degraded by R. palustris. Utilization of these feedstocks can reduce the industry cost and is beneficial for environment. Applications of R. palustris for biopolymers and their building blocks production, and biofuels production are discussed. Afterward, some novel applications in microbial fuel cells, microbial electrosynthesis and photocatalytic synthesis are summarized. The challenges of the application of R. palustris are analyzed, and possible solutions are suggested.